Metallocene Polyolefins Reinforced by Low-Entanglement UHMWPE through Interfacial Entanglements - Xin Tang; Jinheng Xing; Xiang Yan; Chunlin Ye; Letian Zhang; Yu Zhang; Baoqiang Shu; Jingshan Mu; Wei Li; Jingdai Wang; Yongrong Yang (Advances in Polymer Technology)
By introducing low-entanglement UHMWPE, the mechanical properties of polyolefins are improved to varying degrees. For polypropylene, the lack of interaction between UHMWPE and polypropylene results in an unsatisfactory reinforcement effect, and the disentangled state makes it easier for the particles to form defects driven by a chain explosion. In contrast, regarding polyethylene and elastomer containing ethylene segments, low-entanglement UHMWPE plays a better role in reinforcement. A series of measurements including scanning electron microscopy (SEM), rheological measurements, differential scanning calorimetry (DSC), and mechanical measurement were used to investigate the mechanisms for the different enhancement effects. It originates from interdiffusion and entanglement forming of polyethylene segments across the interface, endowing the material with different aggregated and defect structures. For instance, EPDM possesses a higher optimal dosage of UHMWPE particles reflected in good interfacial interdiffusion with UHMWPE particles, leading to significant optimized mechanical performance.